2013
DOI: 10.3189/2013jog12j182
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Greenland Ice Sheet Projections to Model Formulations

Abstract: ABSTRACT. Physically based projections of the Greenland ice sheet contribution to future sea-level change are subject to uncertainties of the atmospheric and oceanic climatic forcing and to the formulations within the ice flow model itself. Here a higher-order, three-dimensional thermomechanical ice flow model is used, initialized to the present-day geometry. The forcing comes from a high-resolution regional climate model and from a flowline model applied to four individual marine-terminated glaciers, and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
172
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(186 citation statements)
references
References 63 publications
(130 reference statements)
14
172
0
Order By: Relevance
“…We tested this concept by repeating our experiments using the VUB-GISM-HO model with SMB determined interactively, using a degree-day model (DDM) (26). Experiments allowed DDM-derived SMB to evolve freely between 2000 and 2200 or held SMB fixed at its DDM-derived value for 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested this concept by repeating our experiments using the VUB-GISM-HO model with SMB determined interactively, using a degree-day model (DDM) (26). Experiments allowed DDM-derived SMB to evolve freely between 2000 and 2200 or held SMB fixed at its DDM-derived value for 2000.…”
Section: Discussionmentioning
confidence: 99%
“…The parameterization was implemented in four different icesheet models: Vrije Universiteit Brussel Greenland Ice Sheet Model (VUB-GISM-HO) (25,26), Elmer/Ice (27), Community Ice Sheet Model (CISM) 2.0 (28), and Model for Prediction Across Scales (MPAS)-Land Ice (29), all of which have higherorder flow physics in which the representation of an ice mass's internal stress distribution is complete or almost complete and no a priori assumption of a local stress balance is made. Details of the individual models, including initialization strategy and numerical implementation, are provided in SI Text.…”
Section: Implementation In Ice-sheet Modelsmentioning
confidence: 99%
“…4) demonstrates the significant and immediate effect of an abrupt change to the transmissive 'membrane' stresses acting across the grounding line on flow dynamics, highlighting the importance of explicitly including variations in the lateral transmissive stresses in model studies. While a number of modelling studies have been published that account for changes in backstress, which can propagate upstream through transmissive horizontal lateral stresses (Joughin and others, 2010;Favier and others, 2014;De Rydt and others, 2015), there are many studies that use a 'flowline' approach (Nick andothers, 2009, 2012;Gladstone and others, 2012;Goelzer and others, 2013). It has been shown that flowline models are deficient in some circumstances including those more complex settings where buttressing effects are important (Gudmundsson and others, 2012;Gudmundsson, 2013).…”
Section: Instantaneous and Dynamic Adjustment Following Ice-shelf Colmentioning
confidence: 99%
“…If and when this temperature threshold is passed depends critically on past and future greenhouse gas emissions Goelzer et al, 2013;Gregory et al, 2004a;Rae et al, 2012). Even if emissions were reduced to zero, temperatures would not drop significantly for thousands of years because of the long lifetime of anthropogenic CO 2 in the atmosphere and reduced oceanic heat uptake if oceanic convection is extenuated (Allen et al, 2009;Solomon et al, 2009;Zickfeld et al, 2013).…”
Section: Introductionmentioning
confidence: 99%